Specific Aspects of The Development of Mountain and Sub-Mountain Regions - Qalandarova M.K. (Scientific Trends, 2023)
In this article, the specific aspects of the development of mountain and sub-mountain areas , the most important elements of the mountain relief, the meaning of the concept of mountain and mountain system, the hierarchically defined levels of the mountain as a scientific concept and their characteristics, the interpretation of the height limits of the natural-social economic altitude zones, and the legal issues related to the formation of the mountain national policy for the sustainable development of the mountain regions of the country are analyzed.
Keywords: mountain, mountain area, mountain range, mountain topography, sustainable development, mountain nature, three-dimensionality of mountain nature, factors of mountain formation, mountains three-dimensional coordinate system, elevation zones, national mountain policy.